Experimental design method to the weld bead geometry optimization for hybrid laser-MAG welding in a narrow chamfer configuration. (March 2017) - Bidi, Lyes; Le Masson, Philippe; Cicala, Eugen; Primault, Christophe
Abstract: The work presented in this paper relates to the optimization of operating parameters of the welding by the experimental design approach. The welding process used is the hybrid laser-MAG welding, which consists in combining a laser beam with an MAG torch, to increase the productivity and reliability of the chamfer filling operation in several passes over the entire height of the chamfer. Each pass, providing 2 mm deposited metal and must provide sufficient lateral penetration of about 0.2 mm. The experimental design method has been used in order to estimate the operating parameters effects and their interactions on the lateral penetration on one hand, and to provide a mathematical model that relates the welding parameters of welding to the objective function lateral penetration on the other hand. Furthermore, in this study, we sought to the identification of the set of optimum parameters sufficient to comply with a constraint on the quality of weld bead. This constraint is to simultaneously obtain a total lateral penetration greater than 0.4 mm and an H/L ratio less than 0.6. In order to obtain this condition, the multi-objective optimization (for both response functions) of a weld bead by the implementation of the plans method using two categories of Experiments Plans, on two levels has been used: the first is a complete experimental design (CED) with 32 tests and the second a fractional experimental design (FED) with 8 tests. A comparative analysis of the implementation of both types of experiments plans identified the advantages and disadvantages for each type of plan. Highlights: Control the hybrid laser-MAG welding process in a narrow groove configuration. Optimization of operating parameters of the welding by the experimental design approach. The lateral penetration is a complex objective function. The effects of the two experiment designs for the case of the lateral penetration of welding beads have been analyzed.